Development of Sound-Absorbing Composites Made from Water Hyacinth Waste and Recycled Cardboard - Anastasya, Agitha; Widyaningsih, Ayu; Firmansyah, Lucky Fathoni (Universitas Negeri Semarang, 2025)
Noise is a factor that can disrupt the comfort and effectiveness of daily activities, including learning. To address this issue, this study develops an environmentally friendly sound-absorbing material made from water hyacinth and cardboard, both of which possess natural porosity suitable for acoustic applications. This experimental research aims to determine the sound absorption coefficient of composite materials produced from various combinations of these wastes. Five composite variations were prepared: Sample A (4 g water hyacinth, 4 g cardboard, 8 g matrix), Sample B (5 g water hyacinth, 3 g cardboard, 8 g matrix), Sample C (3 g water hyacinth, 5 g cardboard, 8 g matrix), Sample D (4 g water hyacinth, 4 g cardboard, 9 g matrix), and Sample E (4 g water hyacinth, 4 g cardboard, 7 g matrix). The absorption coefficient was measured using an impedance tube. The results showed that each composition produced different absorption coefficients. Sample D, with a composite-to-matrix ratio of 7:9, had the highest sound absorption coefficient of 0.327 at a frequency of 100 Hz. Meanwhile, Sample E, with a composite-to-matrix ratio of 9:7, had the lowest coefficient of 0.014 at 350 Hz. The findings indicate that water hyacinth and cardboard can be utilized as sound-absorbing materials, with absorption coefficients ranging from 0.01 to 0.32, thereby meeting the ISO 11654 standard.